Effects of different frequencies of repetitive transcranial magnetic stimulation in stroke patients with non-fluent aphasia: a randomized, sham-controlled study. (3rd June 2018) - Hu, Xue-yan; Zhang, Tong; Rajah, Gary B.; Stone, Christopher; Liu, Li-xu; He, Jing-jie; Shan, Lei; Yang, Ling-yu; Liu, Ping; Gao, Fei; Yang, Yu-qi; Wu, Xiao-li; et al.
ABSTRACT: Objective: The purpose of this study was to compare the efficacy of repetitive transcranial magnetic stimulation (rTMS) applied at different frequencies to the contra-lesional hemisphere to optimize the treatment of post-stroke non-fluent aphasia. Method: Patients with post-stroke non-fluent aphasia were divided randomly into four groups: a high-frequency rTMS (HF-rTMS) group (10 Hz), a low-frequency rTMS (LF-rTMS) group (1 Hz), a sham stimulation group, and a control group. All groups received the standard treatment (consisting of drug therapy, conventional physical exercises, and speech training); in the HF-rTMS and LF-rTMS, this was supplemented with magnetic stimulation that targeted the mirror area within the right hemispheric Broca's area. Patients' language ability was assessed prior to, immediately after, and at 2 months post-treatment by the Chinese version of the Western Aphasia Battery (WAB). Results: When measured immediately post-treatment, as well as at 2 months post-treatment, the LF-rTMS group exhibited a more marked improvement than the HF-rTMS group in spontaneous speech, auditory comprehension, and aphasia quotients (AQ). Compared to the control group, the HF-rTMS cohort exhibited significant improvement at 2-months post-treatment in repetition and AQ. Conclusions: LF-rTMS and HF-rTMS are both beneficial to the recovery of linguistic function in patients with post-stroke non-fluent aphasia. LF-rTMS produced immediate benefits that persisted long-term, while HF-rTMS only produced long-term benefits. In addition, the benefits produced with LF-rTMS were more marked than those produced by HF-rTMS.